ECONOMIC MODELS OF INCREASING EMPLOYMENT THROUGH DEVELOPMENT OF SERVICE INFRASTRUCTURE IN REGIONS (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article scientifically analyzes economic models for increasing employment through the development of service infrastructure in the regions. The study identifies the relationship between the territorial development of the service sector, the level of infrastructure provision and employment indicators. The role of the expansion of service infrastructure in creating new jobs, effective use of labor resources, and reducing interregional socio-economic disparities is revealed. The article examines economic models based on clustering, digital infrastructure, public-private partnerships, and the service economy on the basis of a systematic approach and substantiates the possibilities of their application in the conditions of the regions of Uzbekistan. The results of the study serve to develop scientific and practical proposals aimed at improving regional employment policy and ensuring the sustainable development of the service sector.
Keywords: service infrastructure, regional development, employment, economic models, service economy, new jobs, public-private partnership, digital infrastructure, regional employment policy.